DETAILED RETINAL IMAGING IN CARRIERS OF OCULAR ALBINISM. Issue 3 (March 2018) - Khan, Kamron N.; Lord, Emma C.; Arno, Gavin; Islam, Farrah; Carss, Keren J.; Raymond, FLucy; Toomes, Carmel; Ali, Manir; Inglehearn, Chris F.; Webster, Andrew R.; Moore, Anthony T.; Poulter, James A.; et al.
Abstract : Background: Albinism refers to a group of disorders primarily characterized by hypopigmentation. Affected individuals usually manifest both ocular and cutaneous features of the disease, but occasionally hair and skin pigmentation may appear normal. This is the case in ocular albinism, an X chromosome linked disorder resulting from mutation of GPR143 . Female carriers may be recognized by a "mud-splatter" appearance in the peripheral retina. The macula is thought to be normal, however. Methods: Obligate female carriers of pathogenic GPR143 alleles were recruited. Molecular confirmation of disease was performed only for atypical cases. Detailed retinal imaging was performed (colour fundus photography, optical coherence tomography, fundus autofluorescence. Results: Eight individuals were ascertained. A novel GPR143 mutation was identified in one family (p.Gln328Ter). Foveal fundus autofluorescence was subjectively reduced in 6/6 patients imaged. A "tapetal-like" pattern of autofluorescence was visible at the macula in 3/6. Persistence of the inner retinal layers at the fovea was observed in 6/8 females. Conclusion: Female carriers of ocular albinism may manifest signs of retinal pigment epithelium mosaicism at the macula and the peripheral fundus. A tapetal-like reflex on fundus autofluorescence may be considered the macular correlate of "mud-splatter." Abstract : Supplemental Digital Content is Available in the Text.Ocular albinism may be mistaken for other disorders associated with congenital nystagmus. The authors identify features of ocular albinism, present in female carriers that will help facilitate an accurate diagnosis.